INTRAORAL SCANNING FOR EARLY DENTAL EROSION ASSESSMENT - AN IN VITRO STUDY - Codruța E. Ille; Andrei B. Faur; Raul N. Rotar; Ioana L. Pîrvulescu; Anca Jivănescu (Romanian Society of Oral Rehabilitation, 2021)
Tooth wear has increased its incidence globally, and erosion was the topic for several research studies. Acidic food and beverages can affect natural teeth, and chronic exposure leads to the development of dental wear. Dentists should use proper diagnostic tools to identify and monitor tooth wear, in order to select the best treatment option. Aim: The current study quantifies the feasibility of using an intraoral scanner to monitor early erosive tooth wear in patients. Materials and methods: 12 sound extracted human molars were scanned initially and after immersion in soft acidic beverage (Coca-Cola) for 1, 3 and 19 h, respectively. The 3D data were uploaded to a specific metrology and inspection software (Geomagic Control X) for comparison. Each scan was superimposed on the reference 3D model, and relevant numerical data were obtained. Results: The results detected statistically relevant differences between the compared 3D meshes, indicating dental tissue loss increasing with the time of exposure in acidic soda. Conclusion: The intraoral scanner used in this experiment was capable to detect minimal dental tissue loss and could be used to monitor early erosive tooth wear.